Los morfemas diminutivos -ico, -illo, -ito, en documentos hispanoaméricanos de América Central y de la Nueva España: siglos XVI y XVII - Mariano Franco Figueroa (Estudios de Lingüística, 1988)
The purpose of this work consists of both offering some inventories of derived voices that present the morphemes -ico, -illo, -ito, and observing their vitality and productive performance in the process of lexical creation begun with the Discovery. We have differenciated the notional meanings of the suffix from those in which the lexicalization of the morpheme has occurred. The statistical results show that -illo is the most often documented suffix, but the one that appears with the highest lexicalization; -ito appears in only a few lexical cases, which proves its high performance as a diminutive. Observing the lexicalization of these two makes evident a larger proportion of americanisms in favour of -illo. The suffix -ico, with a high percentage of lexicalized words, is of low performance. The group formed by these three facultative morphemes would show that since the very first moment of the colonization, -ito goes on working with its originary sense of diminution and illo, because of the vast majority of documented terms, would corroborate the Andalusian settlers' inflow and that this is preferred when they want to add different values from the notional one, even in the case of proper nouns.